The phenomenon of cyber begging in the perspective of pancasila character values - Yuniar Mujiwati; Ayu Maya Damayanti; Khamdan Safiudin (Universitas Tanjungpura, 2023)
The phenomenon of cyber begging or online begging has mushroomed the spectrum of society when the pandemic hit. This social behavior infects all communal layers regardless of status and class. Of course, if this is allowed to continue, it will become a threat to the state, not only attacking economic empowerment, but also becoming a disease that can injure and injure the values of the Pancasila character. So that the phenomenon of cyber begging will be reviewed and studied based on the perspective of Pancasila character values. The basic premise of writing this article is an in-depth review of the phenomenon of cyber begging that occurs in today's digital society. Followed by a study of cyber begging from the point of view of the values of character education, which turns out to be a threat to the character of society at large, thus contradicting the purpose of Pancasila character education itself. This article will answer how in the end the phenomenon of cyber begging cannot be justified even if it is caused by economic factors because the government itself has been progressive in making programs to empower the people's economy, even unexpectedly there are still many people with no character and mentality of beggars who still roam the digital world to carry out the action of begging online when in fact it is not justified from the point of view of Pancasila character values